2016
DOI: 10.3329/bjar.v40i4.26932
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ethephon on ripening and quality of winter tomato fruit harvested at different maturity stages

Abstract: An experiment taking tomato fruits (cv. BARI Tomato-14) of three maturity stages (mature green stage, breaker stage and half ripen stage) and four ethephon levels [control (distilled water spray), 500, 750 and 1000 ppm] was carried out at the laboratory of plant physiology section of Horticulture research centre, Bangladesh Agricultural Research Institute) during February 14, 2013 to February 27, 2012 to find out the suitable stage of fruit maturity for post harvest application of ethephon (ethrel) for tomato … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
3
5
0
Order By: Relevance
“…Higher TSS content represents more ripeness of fruits among ripe fruits of the same variety [26]. The findings in this study is in consonance with the results were observed in tomato [4,14,27,28] and pear [21].…”
Section: Effect Of Ethephon On Physicochemical Parameter Of Tomatosupporting
confidence: 92%
See 3 more Smart Citations
“…Higher TSS content represents more ripeness of fruits among ripe fruits of the same variety [26]. The findings in this study is in consonance with the results were observed in tomato [4,14,27,28] and pear [21].…”
Section: Effect Of Ethephon On Physicochemical Parameter Of Tomatosupporting
confidence: 92%
“…The increased permeability of the membrane allows the acids stored in the cell vacuoles to breathe at a higher rate [4]. The similar observations were reported in tomato [4,14], banana [9] and mango [23].…”
Section: Effect Of Ethephon On Physicochemical Parameter Of Tomatosupporting
confidence: 68%
See 2 more Smart Citations
“…al., 2018;Gurjar et al, 2017;Sukhjit, 2017 ), banana (Mahajan et. al., 2010), tomato (Moniruzzaman et. al., 2015), guava (Mahajan et.…”
Section: Introductionmentioning
confidence: 99%